2010
DOI: 10.3109/02770903.2010.493966
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of an Interactive Voice Response Telephone System and Specialist Nurse Support for Childhood Asthma Management

Abstract: This study suggested that both IVR and Nurse Support interventions may be cost-saving from a health system perspective, with IVR providing the greatest benefit and this pilot study provides a strong basis for developing larger trials with longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…These same arguments can be extended to automated telephone interventions such as CareCall as a supplemental method to traditional rehabilitation, especially given the evidence that users do indeed form relationships with the IVR system as they would with a 'live' person. 8 A major strength of automated interventions similar to CareCall is their potential for substantial health-care cost-savings, 22 given that most traditional telephone follow up occurs at specialty medical facilities requiring dedicated staff and resources. Importantly, Xu et al 22 demonstrates savings may be achieved with little loss in efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These same arguments can be extended to automated telephone interventions such as CareCall as a supplemental method to traditional rehabilitation, especially given the evidence that users do indeed form relationships with the IVR system as they would with a 'live' person. 8 A major strength of automated interventions similar to CareCall is their potential for substantial health-care cost-savings, 22 given that most traditional telephone follow up occurs at specialty medical facilities requiring dedicated staff and resources. Importantly, Xu et al 22 demonstrates savings may be achieved with little loss in efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…8 A major strength of automated interventions similar to CareCall is their potential for substantial health-care cost-savings, 22 given that most traditional telephone follow up occurs at specialty medical facilities requiring dedicated staff and resources. Importantly, Xu et al 22 demonstrates savings may be achieved with little loss in efficacy. A further strength over traditional telephone follow up is CareCall's ability to identify unmet needs even many years post diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…IVRs have demonstrated some efficacy in chronic disease management, including screening, preventive services, and medication adherence [15][16][17]. IVR can obtain information from patients, deliver tailored instructions, and allow for remote monitoring [18]. Previous studies of IVR interventions have used quasi-experimental designs [19,20] and clinical trials [16,21] but have had mixed results; very little rigorous work has been done to evaluate IVR interventions focused on care transitions; thus a rigorous, real-world study of an IVR-based intervention to support care transitions in congestive heart failure (CHF) and chronic obstructive pulmonary disease (COPD) was needed.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to deduce which type of intervention is the most effective, because none yielded consistent results. Except for 3 studies that found no significant differences between their comparators8,74,76, findings from other studies showed that these interventions benefited all severity levels of asthma (from mild to potentially fatal asthma).…”
Section: Background Of Reviewed Studiesmentioning
confidence: 95%
“…The majority of the studies originated from the United States of America7,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54, followed by Europe8,55,56,57,58,59,60,61,62,63,64,65,66,67, Asia68-72, and Australia 73,7475,76. There was one economic evaluation concerning enhanced asthma management30 done in 1991, and at least one between 1994 and 2012.…”
Section: Background Of Reviewed Studiesmentioning
confidence: 99%